Introduction of biosimilar insulins in Europe - Davies, M.; Dahl, D.; Heise, T.; Kiljanski, J.; Mathieu, C. (Diabetic medicine, 2017)
Regulatory approval of the first biosimilar insulin in Europe, LY2963016 insulin glargine (Abasaglar®), in 2014 expanded the treatment options available to people with diabetes. As biosimilar insulin products come to market, it is important to recognize that insulin products are biologicals manufactured through complex biotechnology processes, and thus biosimilar insulins cannot be considered identical to their reference products. Strict regulatory guidelines adopted by authorities in Europe, the USA and some other countries help to ensure that efficacy and safety profiles of biosimilar insulins are not meaningfully different from those of the reference products, preventing entry of biological compounds not meeting quality standards and potentially affecting people's glycaemic outcomes. This review explains the concept of biosimilar medicines and outlines regulatory requirements for registration of biosimilar insulins in Europe, which is illustrated by the successful development of LY2963016 insulin glargine and MK‐1293 insulin glargine (Lusduna®). Preclinical and clinical comparative studies of the biosimilar insulin glargine programmes include in vitro bioassays for insulin and insulin‐like growth factor 1 receptor binding, assessment of in vitro biological activity, evaluation of pharmacokinetic/pharmacodynamic profiles in phase I studies and assessment of long‐term safety and efficacy in phase III studies. The emergence of biosimilar insulins may help broaden access to modern insulins, increase individualized treatment options and reduce costs of insulin therapy.